The Effect of Implicit Followership Antecedents on the New Generation of Individuals - Lu, Kunxiu; Zhang, Wei; Zhang, Xiaoyan; Feng, Junshu; Li, Ying (Frontiers in Psychology, 2022)
Implicit followership refers to the assumptions and schemas that individuals have on the traits and behaviors that followers should possess. It is the cognitive basis for organizational members to understand and respond to followers’ behaviors. This study is based on the study of the propensity proposition of implicit followership, and explores the effect of individual proactive personality and core self-evaluation on the implicit followership of different schemas. Through analysis and collection of 451 university graduates from a certain undergraduate college, the intertemporal survey data of one month interval, this study found that core self-evaluation can significantly positively affect positive implicit followership, and significantly negatively affect negative followership. The results of data analysis support the interpretation of propensity propositions in the study of personality traits. This study also discusses the theoretical significance and practical application value.